A SHORT RIB POLYDACTYLY SYNDROME OVERLAPPING BOTH LETHAL AND NONLETHAL TYPES - (:unkn) unknown (MEDECINE ET HYGIENE, 2012)
A short rib polydactyly syndrome overlapping both lethal and nonlethal types: Short rib polydactyly syndrome (SRPS) type II is a rare, autosomal recessively inherited, lethal skeletal dysplasia characterized by polydactyly, short limbs, short and horizontal ribs, a short ovoid tibia and major organ anomalies. We report a patient with a fetus with SRPS type II that presented at the 19th week of pregnancy for amniocentesis because of maternal age. During ultrasound pre-axial synpolydacytly, a short and ovoid tibia, nuchal edema, vertebral irregularities, hypoplastic thorax with short ribs and talipes were detected. All of the extremities were under the 5th percentile. Thorax-abdomen ratio was 0,56. The family was counselled for a diagnosis of lethal SRPS. After termination of pregnancy, radiological and histopathological examination allowed us to reach the diagnosis of Majewski syndrome (SRPS type II). SRPSs are a continuous spectrum of both lethal and nonlethal forms. Prenatal diagnosis and termination depending on ultrasound findings should be done very precociously considering different phenotypic expressions, even in families previously affected by a lethal SRPS.
Keywords: Majewski syndrome; Short-rib polydactyly syndrome; Ellis van Creveld syndrome; Jeune syndrome; VAN-CREVELD-SYNDROME; MUTATIONS; DIAGNOSIS; SPECTRUM; EVC